A Goal Oriented Navigation System Using Vision - Serdar Güzel, Mehmet; Nattharith, Panus; S. Duran, Ahmet (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper addresses a goal oriented navigation framework in a behavior-based manner for autonomous systems. The framework is mainly designed based on a behavioral architecture and relies on a monocular vision camera to obtain the location of goal. The framework employs a virt ual physic based method to steer the robot towards the goal while avoiding unknown obstacles, located along its path. Simulation results validate the performance of the proposed framework.